"Donation Champion" Training Sessions Increase Hospital Referrals by 113% and Donors by 45% Since 2005. (August 2017) - O'Shaughnessy, Gweneth; Schimpf, Christopher; Reynolds, Andrea; Hasz, Richard; Nathan, Howard
Abstract : Introduction: In the U.S., OPOs provide education about the donation process for hospital personnel. Their knowledge of donation best-practices, as well as advocacy for collaborative partnership with the OPO, are essential to facilitating the donation process. Methods: The OPO has constructed a full-day seminar offering 6.5 continuing educations units (accredited by AACN and AARC. Fifteen to seventeen sessions are held annually at centralized locations including the OPO's state-of-the-art conference center and at large transplant hospitals and conference centers throughout the region. The agenda includes plenary sessions on medical management and brain death communication, donor family and recipient panel discussions, breakouts on donation after circulatory death, and family communication, expert advice from hospital-based nursing leaders and surgeons, and discussion about the leadership role attendees have earned as they become "Donation Champions". The focus of the day is on timely referral of potential donors to the OPO, clinical support of potential donors, DCD, and a collaborative, planned approached to family conversations about donation. Messaging developed for these training sessions is regularly reinforced during all standard OPO hospital development programming. Results: The first seminar was held in 2006. Through 12/31/2016 110 training sessions were held, reaching 7, 877 nurses and respiratory therapists from 159 hospitals. Pre data (2005) and post data (2016) was analyzed. The number of ventilator dependent patients referred annually more than doubled, increasing by 2, 531 (113%). The OPO's referral rate increased from 80% to 99%; while the number of missed referrals dramatically declined from 20% in 2005 to 1% in 2016. The number of organ donors increased by 158 (45%) during the same timeframe. Conclusion: These expansive offerings and their constant reinforcement have dramatically improved OPO performance and organ donation outcomes. Although there are other factors that may have influenced this record of success, this is one key educational change that the OPO instituted to impact improved regional performance. Figure. No caption available.